PERBANDINGAN EFISIENSI TRANSAKSI UANG DIGITAL DAN UANG TUNAI DI INDONESIA - Hanaya Tri Meyharin Sihotang; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is to compare the transaction efficiency between digital money and cash in the context of daily use in Indonesia. The method used is descriptive quantitative analysis by collecting data through surveys and interviews with consumers who frequently use both types of payments. Efficiency is measured based on the time required to make transactions, transaction costs, and user convenience in using digital money and cash. The results show that transactions using digital money are more efficient in terms of time and operational costs compared to using cash, especially in long-distance and small-amount transactions. On the other hand, while cash is still dominant in direct physical transactions, digital money offers advantages in terms of speed and convenience, especially with the growing digital infrastructure in Indonesia. This study concludes that while cash still has an important role to play, digital money shows great potential in improving the efficiency of economic transactions, both in terms of individuals and the payment system as a whole.